Semantic evolution of the lexeme park in the Polish language (in appellatives and proper names) - Myszka, Agnieszka (Papers in Linguistics, 2025)
New technologies, the changing space around us as well as social and cultural transformations entail changes in language. New lexemes or phrases are created, while the meaning of existing words changes or gets extended (neosemantisations, semantic borrowings), new structures modelled on English, the contemporary lingua franca, are created (loanwords, calques and hybrids). The article concerns lexical changes that took place in the word park, which was borrowed from Latin in the 16th century. The analysis addressed directions of these changes and their causes and mechanism. It included first of all instances of proper names containing the word park in their structure, but also its appellative applications. In the final part an attempt was made to construct a contemporary definition of this lexeme.